Chronic Energi Deficiency Factor`s In Pregnant Women: Literature Review - Anis Permanasari; Reni Zuraida; Wuryaningsih Dwi Sayekti (CV. AFDIFAL MAJU BERKAH, 2024)
Chronic Energy Deficiency (CED) is one of the condition in where woman age fertile (WUS) experience lack nutrition ( calories and protein) that lasts a long time or chronic . Someone own risk KEK If have size LILA < 23.5 cm. Research method search article This use from Google Scholar and PubMed which then conducted a review with keywords not enough energy chronic and mother pregnant , selected articles​ is article Indonesian and English English as many as 8 journals that can be accessed . Research results obtained that intake energy , intake carbohydrates , fat intake , protein intake , disease infections that occur in mothers , education mother , job mother, income family , nutritional status before pregnant , and age Mother is factor risk occurrence of KEK in mothers pregnant.